Speed behaviour and mental workload of small-spacing expressway interchanges based on field driving test. - Xu, Jin; Chen, Zheng-Huan; Kong, Fan-Xing; Zheng, Zhan-Ji; Zhang, He-Shan; Wang, Yan-Peng (Ergonomics, 2024)
Many small-spacing interchanges (SSI) appear with the improvement of the expressway network. To investigate the speed and mental workload characteristics in the SSI and acquire the mechanism of the influence of speed on the drivers' workload, 37 participants were recruited to perform a field driving test. Each driver performed four driving conditions (i.e. ramp-mainline, mainline-ramp, mainline driving, and auxiliary lane driving). The speed and drivers' electrocardiogram (ECG) data were collected using SpeedBox speed acquisition equipment and PhysioLAB physiological instrument. The heart rate increase (HRI) index was used to analyse the drivers' mental workload regularity. The relationship model between speed and HRI was developed to examine the impact of speed on HRI. The results show that the speed variation in the SSI displayed two patterns: 'decrease - increase and continuous decrease.' The drivers' HRI variation presented four patterns: 'convex curve, continuously increasing, continuously decreasing and concave curve'. SSI's influenced area length is given based on the speed and HRI variation regularity. HRI is significantly higher when driving in the ramp-mainline condition in the SSI than when driving in other conditions, indicating that drivers are more nervous when merging with the mainline traffic. HRI increases significantly in the first 50% of the weaving area in four driving conditions, indicating that vehicle weaving greatly influences the drivers' mental workload. A positive correlation exists between vehicle speed and drivers' HRI without interference from other vehicles and road alignment. The shorter spacing of the interchange will result in a more difficult driving task for the drivers. This study shows that drivers have the highest mental workload in ramp-mainline driving condition at small-spacing interchanges. The first half of the weaving area is the area where drivers' mental workload increases significantly, and is a high-risk section for small-spacing interchanges. This study can provide a reference for the revision of the allowable minimum interchange spacing in the corresponding specification, and the calibration of the simulation test parameters for similar scenarios.